Return to retail banking and payments - Iftekhar Hasan; Heiko Schmiedel; Liang Song (European Central Bank (ECB), 2009)
The European banking industry joined forces to achieve a fully integrated market for retail payment services in the euro area: the Single Euro Payments Area (SEPA). Against this background, the present paper examines the fundamental relationship between retail payment business and overall bank performance. Using data from across 27 European markets over the period 2000-07, we analyse whether the provisions of retail payment services are reflected in improved bank performance, using accounting ratios and efficiency measures. The results confirm that the performance of banks in countries with more developed retail payment service markets is better. This relationship is stronger in countries with a relatively high adoption of retail payment transaction technologies. Retail payment transaction technology itself can also improve bank performance, and evidence shows that heterogeneity in retail payment instruments is associated with enhanced bank performance. Similarly, a higher usage of electronic retail payment instruments seems to stimulate banking business. We also show that retail payment services have a more significant impact on savings and cooperative bank performance although they have a positive influence on the performance of commercial banks. Additionally, findings reveal that impact of retail services on bank performance is dominated by fee income. Finally, an effective payment service market is found to be associated with higher bank stability. Our findings are robust to different regression specifications. The results may also be informative for the industry when reconsidering its business models in the light of current financial market developments.
Keywords: G21; G28; 330; bank performance; cost and profit efficiency; retail payment; Bargeldloser Zahlungsverkehr; Bankgeschäft; Privatkundengeschäft; Rentabilität; EU-Staaten